The comparison of the lumbopelvic stabilizer muscle endurance in female athletes with and without patellofemoral pain syndrome - Elham Mohamadi; Reza Rajabi; Mohammad Hussein Alizadeh (Vesnu Publications, 2013)
Introduction: Decreased hip muscles strength has been implicated to lower-extremity malalignment and patellofemoral pain. Proximal muscle groups including the lumbopelvic stabilizer muscles are responsible for postural control and body stability. Strengthening in these keys muscles have not been investigated in previous studies. The purpose of this study was to compare the lumbopelvic stabilizer muscles endurance in female athletes with and without patellofemoral pain syndrome. Materials and Methods: Thirty female athletes diagnosed with patellofemoral pain syndrome (mean ± SD age; 21.60 ± 2.75 year, mean ± SD weight; 60.70 ± 8.70 kg, mean ± SD height; 165 ± 0.073 cm) and thirty asymptomatic females athletes (mean ± SD age; 20.77 ± 2.63 year, mean ± SD weight; 60.53 ± 6.66 kg, mean ± SD height; 164 ± 0.063 cm) with history of 3 years participating in volleyball, basketball or handball training were recruited in this study. The protocol established by McGill was used to determine the muscle endurance of the lumbopelvic stabilizer muscles. The protocol consists of four tests that measure all aspects of the torso via isometric muscle endurance: trunk flexor test, trunk extensor test (Biering Sorensen test), left and right lateral musculature tests (Side bridge test). Data were analyzed using the independent samples t-test in SPSS software. The significance level set at P < 0.05. Results: The results showed a statistically significant difference between two groups for lumbopelvic stabilizer muscles endurance (P = 0.001). The greatest differences were found in anterior part of the lumbopelvic muscle endurance (abdominal muscles). The results indicated that young women with patellofemoral pain are less likely to demonstrate endurance in lumbopelvic stabilizer muscles than age-matched control group women who are not symptomatic. Conclusion: The lumbopelvic stabilizer muscles endurance training would be proposed for prevention and treatment of patellofemoral pain. Keywords: Patellofemoral pain syndrome, Female athletes, Lumbopelvic stability, Endurance muscles